2019
DOI: 10.1002/ange.201911606
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Directed Rare‐Earth Separations

Abstract: The separation of rare-earth ions from one another is challenging due to their chemical and physical similarities. Nearly all rare-earth separations rely upon small changes in ionic radii to direct speciation or reactivity.H erein, we show that the intrinsic magnetic properties of the rare-earth ions impact the separations of light/heavy and selected heavy/heavy binary mixtures.U sing TriNOx 3À ([{(2-t BuNO)-C 6 H 4 CH 2 } 3 N] 3À )r are-earth complexes,w ee fficiently and selectively crystallized heavy rare e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Detection of Nd 3+ , Sm 3+ , and Dy 3+ by adjusting the procedure presented may be implemented also for the recovery of these important lanthanides. These elements are used on a large scale in rare-earth-based magnets, and significant research focuses on their recycling. , Therefore, the process developed has potential for the detection of other relevant lanthanides, such as Nd 3+ , Sm 3+ , Dy 3+ , and Yb 3+ . This can be achieved by varying and optimizing the eluent system including the dissolved sensitizer ligand for each of these elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of Nd 3+ , Sm 3+ , and Dy 3+ by adjusting the procedure presented may be implemented also for the recovery of these important lanthanides. These elements are used on a large scale in rare-earth-based magnets, and significant research focuses on their recycling. , Therefore, the process developed has potential for the detection of other relevant lanthanides, such as Nd 3+ , Sm 3+ , Dy 3+ , and Yb 3+ . This can be achieved by varying and optimizing the eluent system including the dissolved sensitizer ligand for each of these elements.…”
Section: Resultsmentioning
confidence: 99%
“…Detection and concentration analysis of critical materials, for example in electronic waste, are important aspects for the evaluation of recycling potential. , Detection of rare earth elements in materials is essential, both for extraction and also for an evaluation of their mining potential by geochemical exploration studies. , Furthermore, after the separation of lanthanide mixtures, quality control is desired, e.g., for Dy 3+ and Nd 3+ , both present in several types of Fe/Nd/B magnets.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a fascinating phenomenon in the formation of enriched rare-earth (RE) ions has repeatedly been observed close to the magnetic source. This potentially unlocks a green separation technology with effective hydrodynamic scales in the μm-particle range in microfluid cells or elevated valorization flux in high-gradient magnetic separators all the way down to the level of ions. The driving force acting on a magnetized body in nonuniform magnetic field is known as Kelvin force.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, magnetic dipole–dipole interaction is utilized for sensing, the self-assembly of magnetic nanoparticles, and geomagnetic-field-directed motile bacteria, e.g., magnetosomes . The Kelvin force functions as the dominating force either in the aqueous phase (by changing the flow pattern which in turn influences the quality of protein crystals) or in the dispersed phase, by directing rare-earth complexes . Further synergized with the Lorentz force, the Kelvin force can support structured electrodeposition by adjusting the concentration boundary layer. …”
Section: Introductionmentioning
confidence: 99%
“… 9 This strategy was used in separating molecular RE-complexes of the [TriNOx] 3− ligand using Fe 14 Nd 2 B permanent magnets ( Chart 1 ). 10 This low energy input separation method allowed for the enhancement of experimental separation factors 11 by approximately 100% for the La/Dy pair. It was also suggested that the achieved separation depended on the free-ion angular momentum ( J = 7.5 for Dy 3+ ) of the trivalent RE cations in its electronic ground state as well as on the monomer–dimer equilibrium that was studied for this system.…”
Section: Introductionmentioning
confidence: 99%